Immigration policy and the search for skilled workers : summary of a workshop - Cohen, Gail Elaine, 1963- (National Academies Press, 2015)
The market for high-skilled workers is becoming increasingly global, as are the markets for knowledge and ideas. While high-skilled immigrants in the United States represent a much smaller proportion of the workforce than they do in countries such as Australia, Canada, and the United Kingdom, these immigrants have an important role in spurring innovation and economic growth in all countries and filling shortages in the domestic labor supply. This report summarizes the proceedings of a Fall 2014 workshop that focused on how immigration policy can be used to attract and retain foreign talent. Participants compared policies on encouraging migration and retention of skilled workers, attracting qualified foreign students and retaining them post-graduation, and input by states or provinces in immigration policies to add flexibility in countries with regional employment differences, among other topics. They also discussed how immigration policies have changed over time in response to undesired labor market outcomes and whether there was sufficient data to measure those outcomes.